2012
DOI: 10.1186/1472-6947-12-14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of decision-support software in carcino-embryonic antigen (CEA)-based follow-up of patients with colorectal cancer

Abstract: BackgroundThe present paper is a first evaluation of the use of "CEAwatch", a clinical support software system for surgeons for the follow-up of colorectal cancer (CRC) patients. This system gathers Carcino-Embryonic Antigen (CEA) values and automatically returns a recommendation based on the latest values.MethodsConsecutive patients receiving follow-up care for CRC fulfilling our in- and exclusion criteria were identified to participate in this study. From August 2008, when the software was introduced, patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 8 publications
(9 reference statements)
1
16
0
Order By: Relevance
“…To help improve the reliability of follow-up of the high volume of test results, electronic result managers have been created—both comprehensive systems98 99 as well as test-specific systems such as tools related to cancer screening or follow-up 100 101. Other approaches target test result follow-up for specific high-risk scenarios such as microbiology cultures pending at the time of discharge from the hospital102 or automatic gastroenterology consultations for positive faecal occult blood tests 103.…”
Section: Resultsmentioning
confidence: 99%
“…To help improve the reliability of follow-up of the high volume of test results, electronic result managers have been created—both comprehensive systems98 99 as well as test-specific systems such as tools related to cancer screening or follow-up 100 101. Other approaches target test result follow-up for specific high-risk scenarios such as microbiology cultures pending at the time of discharge from the hospital102 or automatic gastroenterology consultations for positive faecal occult blood tests 103.…”
Section: Resultsmentioning
confidence: 99%
“…The software support has been shown to be safe and efficient. 22 Internationally, CT scanning is common practice and ultrasound with thoracic X-ray which seem a bit oldfashioned. However this study is performed to compare the usual follow-up with a new schedule; the study was performed during the time that the 2008 Dutch national guideline was used and this guideline advised X-ray and ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies targeted multiple specialisms; the others focused on one specialism. CDSSs of included studies focused on risk assessment or therapy options to support informed decisions [26][27][28][29][30][31][32], as well as statistical methods and data mining to generate patient-specific recommendations [33,34]. For most studies (7/9), clinical guidelines formed the knowledge base of the CDSS.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…Six studies reported process outcomes ( Table 2). The issues addressed included: use of CSF to control chemotherapy-induced febrile neutropenia [26,27], physician-prescribing behavior [32], clinical trial rate [32], attainment of analgesia [28], time to analgesia [28], frequency of pharmaceutic intervention and pain assessment [28], costs [33] and workload [31]. Comparators included usual care, based on either MDT decisions or clinical guidelines.…”
Section: Process Outcomesmentioning
confidence: 99%